Innate Immune Training of Human Macrophages by Cathelicidin Analogs - van Dijk, Albert; Anten, Jennifer; Bakker, Anne; Evers, Noah; Hoekstra, Anna T.; Chang, Jung-Chin; Scheenstra, Maaike R.; Veldhuizen, Edwin J. A.; Netea, Mihai G.; Berkers, Celia R.; Haagsman, Henk P. (Frontiers in Immunology, 2022)
Trained innate immunity can be induced in human macrophages by microbial ligands, but it is unknown if exposure to endogenous alarmins such as cathelicidins can have similar effects. Previously, we demonstrated sustained protection against infection by the chicken cathelicidin-2 analog DCATH-2. Thus, we assessed the capacity of cathelicidins to induce trained immunity. PMA-differentiated THP-1 (dTHP1) cells were trained with cathelicidin analogs for 24 hours, and restimulated after a 3-day rest period. DCATH-2 training of dTHP-1 cells amplified their proinflammatory cytokine response when restimulated with TLR2/4 agonists. Trained cells displayed a biased cellular metabolism towards mTOR-dependent aerobic glycolysis and long-chain fatty acid accumulation and augmented microbicidal activity. DCATH-2-induced trained immunity was inhibited by histone acetylase inhibitors, suggesting epigenetic regulation, and depended on caveolae/lipid raft-mediated uptake, MAPK p38 and purinergic signaling. To our knowledge, this is the first report of trained immunity by host defense peptides.